If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -54 = 3x + -7x + -6 Reorder the terms: -54 = -6 + 3x + -7x Combine like terms: 3x + -7x = -4x -54 = -6 + -4x Solving -54 = -6 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -54 + 4x = -6 + -4x + 4x Combine like terms: -4x + 4x = 0 -54 + 4x = -6 + 0 -54 + 4x = -6 Add '54' to each side of the equation. -54 + 54 + 4x = -6 + 54 Combine like terms: -54 + 54 = 0 0 + 4x = -6 + 54 4x = -6 + 54 Combine like terms: -6 + 54 = 48 4x = 48 Divide each side by '4'. x = 12 Simplifying x = 12
| 8/24=n/18 | | -9=v-2-2 | | f(x)=4x^5-2x^4+30x^3-15x^2+50x-25 | | 3+6x-x=28 | | 2x^8=15 | | Y=ln(x^2-6x-2) | | 4+3x-5x=4 | | 935/1000 | | 15(x+1)-7(x+9)=4 | | 6y+4=7y-4 | | 3x+20+x+16=180 | | 1/5f=-/5 | | 12+7y=-6 | | 3(5n-5)+3n= | | 2(8)+y=35 | | a-44=72 | | -9+3(8)=15 | | -36x=-5(3x+7) | | x=4+sqrt(4y-4) | | 7/9=70/n | | 25x(x+1)=66 | | 2x+23=4x-19 | | 3x-5x+8=0 | | Y^2-1/64=0 | | -9+38=15 | | 2(7)+y=35 | | 36=10v-v | | X^2-13-130=0 | | 8616/12= | | X-37=35-2x | | 116(3n)=500 | | 21=4u+3u |